2017
DOI: 10.1038/srep41012
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of serum cystatin C for acute kidney injury in adults: a meta-analysis of prospective cohort trials

Abstract: The role of serum cystatin C (Scys) for the detection of acute kidney injury (AKI) has not been fully discussed. This meta-analysis was aimed to investigate the overall diagnostic accuracy of Scys for AKI in adults, and further identify factors affecting its performance. Studies before Sept. 2016 were retrieved from PubMed, Embase, Web of Science and the Cochrane Library. A total of 30 prospective cohort studies (involving 4247 adults from 15 countries, 982 patients occurring AKI) were included. The revised Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 59 publications
(82 reference statements)
5
49
0
4
Order By: Relevance
“…Moreover, the serum CysC level is less dependent on age, sex, race, and muscle mass compared to serum creatinine. Therefore, serum CysC could be an optimal marker, not only for the diagnosis of chronic kidney disease, but also for predicting AKI [12]. Zhang et al [20] performed a retrospective study, and showed that higher serum CysC is associated with poor renal recovery and a longer dependence on CRRT in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the serum CysC level is less dependent on age, sex, race, and muscle mass compared to serum creatinine. Therefore, serum CysC could be an optimal marker, not only for the diagnosis of chronic kidney disease, but also for predicting AKI [12]. Zhang et al [20] performed a retrospective study, and showed that higher serum CysC is associated with poor renal recovery and a longer dependence on CRRT in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be a better biomarker to prediction all-cause AKI based on its half-life, which is shorter than that of serum creatinine [12,13]. Moreover, neutrophil gelatinase-associated lipocalin (NGAL) has been shown to be an early biomarker for predicting AKI before serum creatinine increases [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is anticipated that these biomarkers will enable earlier diagnosis of AKI and facilitate prognostication [10-13, 17, 18]. Among these novel biomarkers, sCyC is considered the most promising functional marker for glomerular filtration [10, 17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…It is anticipated that these biomarkers will enable earlier diagnosis of AKI and facilitate prognostication [10-13, 17, 18]. Among these novel biomarkers, sCyC is considered the most promising functional marker for glomerular filtration [10, 17, 18]. Wan et al [23] reported that the predictive value (the area under the ROC curve, AUC) of sCyC was 0.974, with high sensitivity and specificity, which were similar in Liu’s [24], Yim’s [25], and other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation